2022
DOI: 10.3390/diagnostics12030588
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Early COVID-19 Pandemic on ST-Segment Elevation Myocardial Infarction Presentation and Outcomes—A Systematic Review and Meta-Analysis

Abstract: Background: The influence of the early COVID-19 pandemic on non-COVID-19 emergencies is uncertain. We conducted a systematic review and a meta-analysis to evaluate the impact of the first months of the COVID-19 pandemic on the presentation, management, and prognosis of patients presenting with ST-segment elevation myocardial infarction (STEMI). Methods: We searched the PubMed, Scopus, and Embase databases from January to August 2020. A meta-analysis of studies comparing the profile, STEMI severity at presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Reasons for the declining incidence of STEMI include stay-at-home orders, a decrease in activities that could trigger STEMI and fear of contracting COVID-19. [13][14][15] Additionally, several studies in European countries observed that the pandemic was associated with a significantly longer ischemia time, including a longer door-to-balloon time and a significant reduction in the number of STEMI patient undergoing PCI. 16,17 Factors associated with delayed management include an increase in transportation time, the need for personal protection equipment and the increased burden on healthcare systems overall.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the declining incidence of STEMI include stay-at-home orders, a decrease in activities that could trigger STEMI and fear of contracting COVID-19. [13][14][15] Additionally, several studies in European countries observed that the pandemic was associated with a significantly longer ischemia time, including a longer door-to-balloon time and a significant reduction in the number of STEMI patient undergoing PCI. 16,17 Factors associated with delayed management include an increase in transportation time, the need for personal protection equipment and the increased burden on healthcare systems overall.…”
Section: Discussionmentioning
confidence: 99%
“…The crisis triggered a care deficit for non-COVID diseases such as acute myocardial infarction, stroke, out-of-hospital cardiac arrest, and sepsis, with delayed diagnoses and treatments due to enhanced hospital screening procedures. Additionally, there was a marked decrease in hospitalizations for non-COVID-19 diseases [ 4 , 5 , 6 , 7 , 8 ]. This was partially caused by hospitals reallocating resources to handle the spike in COVID-19 cases, and partially because patients delayed or refused treatment for fear of contracting the virus in the healthcare facility [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This caused a gap in care for non-COVID-19 diseases, including delays in diagnosis and treatment due to additional screening processes in hospitals and emergency care systems [5]. The pandemic also impacted emergency medical services for diseases such as acute myocardial infarction, stroke, out-of-hospital cardiac arrest, and sepsis [3,4,[6][7][8][9]. During the pandemic, the epidemiological characteristics of known diseases have also changed.…”
Section: Introductionmentioning
confidence: 99%